The present and the future of benzydamine: expert opinion paper - Bossi, Paolo; Gurizzan, Cristina; Guntinas-Lichius, Orlando; Hainarosie, Razvan; Lancini, Davide (Frontiers in Oral Health, 2023)
Objectives Benzydamine is a compound indicated in the treatment of symptoms of irritation/inflammation of the oropharyngeal cavity, including those associated with pain. Objectives of this expert opinion narrative review is to summarize current indicated benzydamine applications and elicit further ones to be explored. Materials and Methods In this expert opinion paper, evidences underlying the mechanism of action and clinical application of benzydamine are reviewed. Insights are also provided on possible new clinical applications of the drug and new formulations. Results Current recognized indications of benzydamine include: relief of symptoms associated with inflammatory conditions of the mouth and oropharynx, symptomatic treatment of gingivitis and stomatitis, oral mucositis induced by chemotherapy and/or radiotherapy and post operative sore throat. In addition, among new applications that need to be explored experts embed: oral lichen planus, burning mouth syndrome, post intubation sore throat, antifungal action and new anticancer target agents induced mucositis. Conclusions Benzydamine is a very versatile compound able to play a auxiliary and adjuvant role in the prevention and treatment of oral cavity/oropharynx disorders. According to experts’ opinion there is the need to design clinical trials to highlight novel possible applications of benzydamine and implemented translational analyses to fine-tune patients’ selection and open future research scenarios.